An assessment of life insurance marketing in Turkey - Bolcakan, Ayşe. (Thesis (Ph.D.)- Bogazici University. Institute for Graduate Studies in Social Sciences, 1994., 1994)
Life insurance is one of the most important sectors in developed economies. It assists capital accumulation, increases savings going into the economy, is a good saving device, and employs a considerable number of people. The individual affiliates with the society's resources in the cases of emergency, by transferring the risk related to the time of death to the insurer. This study provides an extensive literature on life insurance, including the concepts, history, development in the West, problems of the sector in the developing economies, marketing mix strategies and the present state of the life insurance market in Turkey. LA three level field survey was carried out to gain insight into the life insurance marketing in Turkey. The data was gathered during February - April 1994, through three different surveys, consisting of 15 insurance companies, 60 agents and 384 consumersJ The Statistical Package for Social Sciences (SPSS) was utilized to analyze data through Frequency Distributions and Cross-Tabulations. The major results of the study are: Most of the insurers are not marketing oriented and do not have formal marketing structure. Since the executives do not consider marketing ft major business function, they are unclear about marketing mix strategies. Mostly, insurers attribute all sectoral problems to consumers or agents. Nearly unanimously, the managers perceive the consumers' attitude to be negative toward insurers. Agents expect to receive brochures, training and marketing support from insurers, however, they do not get sufficient documents and regular and frequent training. Consumers' motives for purchasing life insurance are perceived differently by consumers and agents. In the study the consumers are found to be aware of life insurance but they do not have information about it. Consumers' attitudes toward life insurers, agents and products are negative. Consumers' main expectation from a life insurance policy is protection. Consumers prefer to purchase policies from insurers or banks, and prefer to pay through direct debitting of bank account. In the last part of the study, the implications are summarized for life insurance companies, consumers, state and for further research. This research, being the first extensive academic study in Turkey analysing the life insurance sector, will serve generative function for future research.
Keywords: Insurance, Life -- Turkey.; Insurance companies.